2003
DOI: 10.1080/13651820310001315
|View full text |Cite
|
Sign up to set email alerts
|

Omental and extraperitoneal abscesses complicating cholecystocolic fistula

Abstract: A detailed literature review failed to demonstrate a previous report of this combination of rare complications of gallbladder disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Indeed, cholecysto-enteric fistulas are relatively rare complications of gallstone disease with perforation, with cholecysto-duodenal fistula being the most common type (70%). Most fistulas form insidiously, and are usually not detected until surgery unless there is associated gallstone ileus [4].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, cholecysto-enteric fistulas are relatively rare complications of gallstone disease with perforation, with cholecysto-duodenal fistula being the most common type (70%). Most fistulas form insidiously, and are usually not detected until surgery unless there is associated gallstone ileus [4].…”
Section: Discussionmentioning
confidence: 99%
“…3,7,8 A sequence of events occurs in acute and chronic inflammation of many different causes, resulting in the inflammation of the adjacent colonic serosal surface and adhesion to the gallbladder. 1,3,6 The ischemic area in the wall of the ga l lbladder or colon becomes gangrenous, and the increased pressure within results in its contents penetrating its own necrotic wall at first and then the wall of the adjacent organs, forming a CCF. 9,10 A spontaneous CCF comprises 10-20% of all biliary enteric fistulas.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 For this reason, if CCF such as pneumobilia is suspected in a patient with multiple gallbladder stones, a thorough radiological evaluation for definite diagnosis is required before treatment. 5,6 We herein report a case of an incidentally discovered asymptomatic CCF that was preoperatively diagnosed and successfully managed using laparoscopic surgery. performed and revealed common bile duct stones and a loss of contour of the gallbladder fundus.…”
Section: Introductionmentioning
confidence: 99%
“…If the cystic duct is obstructed, gallbladder and fistula will not be visualised by ERCP (as in our case). Biliary nuclear scintigraphy may delineate the fistula but false-positive and false-negative studies have been reported (22).…”
Section: Discussionmentioning
confidence: 99%